Temporal rate of postmortem DNA degradation in archived tissue samples: evidence from liver and muscle - Amarilla-Stevens, Heidi N.; Stevens, Richard D.; Phillips, Caleb D.; Bradley, Robert D. (Journal of mammalogy, 2023)
Guidelines identifying best practices for harvesting tissues that lead to optimal DNA preservation are few but are important curatorial concerns for genetic resource collections. We conducted a temporal study to establish rate of DNA degradation of tissue samples extracted from field-caught museum specimens. Five individuals of Sigmodon hispidus were collected and their liver and muscle tissues were harvested. Each tissue type was sectioned into 15 subsamples, and each was preserved in liquid nitrogen at different time intervals (2, 4, 8, 16, and 32 min; 1, 2, 4, 8, and 16 h; and 1, 2, 4, 8, and 16 days) following death. DNA was extracted using an automated robotic instrument and molecular mass profiles were determined fluorometrically. Postmortem DNA degradation was continuous and dependent on time, but also was significantly affected by differences among individual cotton rats. DNA fragments of ≥10,000 base pairs in length were present in muscle samples across all time intervals, whereas DNA fragments of this size in liver samples were no longer present after 8–16 h postmortem. DNA molecular mass profiles showed that muscle samples retained 80% of their longest fragments (≥10,000 base pairs) until 1 day postmortem, whereas liver samples retained the same percentage only until 8 min after death. Although rates of decay were measured from samples in a laboratory (not field) setting, rates of decay presented here can guide field and museum workers in best practices. Results suggest that opportunistic samples, such as those from roadkill specimens, are more likely to be of use for a variety of molecular methods when muscle is preserved. Considerations of differences in rates of degradation may also guide selection of tissue types housed in genetic resource collections, especially under space-limited circumstances.